Application of Indonesian's National Standard for Grouping of Bali Cattle with Cluster and Biplot Analysis - Sampurna, I Putu; Nindhia, Tjokorda Sari; Susari, Ni Nyoman Werdi; Suatha, I Ketut (Journal of Veterinary and Animal Sciences; Vol 3 No 2 (2020), 2020)
Research on the application of the Indonesian National Standard (SNI) of Bali cattle by cluster analysis and biplot aims to provide a visual picture in the form of tables and graphs, so that it is easier and faster and more communicative in making decisions, whether the cows studied are included in class I, class II, or class III based on SNI Bali cattle. This study was conducted on 70-year-old adult female cows of 70 animals raised at the Integrated Farming System (Simantri) in Badung regency. The data obtained were analyzed by cluster analysis and biplot, as variables were shoulder height, body length and chest circumference, while as objects were 70 adult cows and 3 classes of Balinese cattle based on SNI of Bali cattle as object identifiers. The results obtained that the application of SNI for Bali cattle can be done by cluster analysis and biplot and both analyzes give the same results to the grouping of Bali cattle objects based on SNI for Bali cattle. Grouping by cluster analysis is easier to see based on the cluster membership obtained, whereas with biplot analysis provides additional information about correlations and diversity between variables.